Feasibility of Conoscopic Holography Measurement in the Stereolithography (SLA) Process with Alumina - Lorenzo Meana; Víctor Meana; Eduardo Cuesta; Pedro Fernández; Gonzalo Valiño; Braulio J. Álvarez (Applied Sciences)
As additive manufacturing technologies continue to gain ground in industrial applications, the need for the accurate metrological evaluation of parts produced with advanced materials becomes increasingly critical. In this context, non-contact metrology plays a key role. This research investigates the performance of conoscopic holography as an optical metrology technique for the inspection of ceramic parts manufactured by stereolithography. However, its reliability needs to be validated, especially as factors such as material properties, surface finish, and color can significantly affect measurement accuracy. Spherical artifacts in alumina were chosen as mathematically well-defined reference elements, and a representative series was produced with the best values for the printing, debinding, and sintering parameters. These spheres were first measured via contact with a coordinate measuring machine (CMM) to establish dimensional (diameter) and geometrical (form error) reference values. These parameters were then compared with measurements obtained via conoscopic holography and optimized by means of Gaussian filters. The results indicated significant dimensional (up to 60 µm) and geometrical (up to 280 µm) deviations from the CMM reference data. The investigation shows that conoscopic holography does not ensure an accurate measurement method for this additive process and ceramic material, making it impossible to achieve power and frequency settings that would allow signal-to-noise ratios above 50%.